Physico-chemical and nutritional properties of maize-cowpea composite gluten-free pasta manufactured by extrusion cooking - Emmambux, Mohammad Naushad (University of Pretoria, 2025)
Dissertation (Msc (Food Science))--University of Pretoria, 2018.